Hybrid spot welding-epoxy bonding of AISI 1008 steel: Shear and nugget analysis - Setyawan, Paryanto Dwi; Hakiki, Irfan; Sugiman, Sugiman; Salman, Salman; Sinarep, Sinarep; Maulana, Andi (Jurnal Polimesin, 2025)
The growing demand for lightweight, high-performance structures in transportation and manufacturing has intensified research on hybrid weld-bonding as a joining method that synergizes the metallurgical strength of resistance spot welding (RSW) with the stress-damping capability of adhesives. However, the interaction between welding parameters, adhesive type, and adhesive thickness and their collective influence on nugget microstructure and joint integrity remains poorly understood. This study addresses these gaps through a systematic parametric investigation of hybrid spot weld–epoxy joints in AISI 1008 steel. Three commercial epoxy adhesives (Araldite 5 min, Araldite 90 min, and Devcon 90 min) were applied at thicknesses of 0.2, 0.6, and 1.0 mm under a fixed RSW schedule (50 A, 10 s), followed by a secondary factorial test varying welding current (50-80 A) and time (10-20 s) for Araldite 5 min at 0.6 mm. Mechanical performance was evaluated via lap shear testing, while fracture morphology and nugget chemistry were analyzed using optical microscopy, SEM, and EDX. Results revealed an optimal configuration at 60 A and 10 s with 0.6 mm Araldite 5 min adhesive, achieving the highest shear strength (~5.74 kN). Strength exhibited a non-monotonic dependence on adhesive thickness, indicating coupled thermo-mechanical effects of polymer decomposition and stress redistribution. Fractographic analysis showed transitions from interfacial to cohesive failure modes with increasing adhesive thickness, while excessive welding energy induced HAZ softening and porosity. The study advances mechanistic understanding by correlating adhesive curing kinetics and thermal degradation with nugget evolution and joint mechanics. These findings provide both scientific insight and practical guidance for optimizing hybrid joining parameters in thin-gauge steel structures.